IMM-H007 promotes hepatic cholesterol and triglyceride metabolism by activating AMPKα to attenuate hypercholesterolemia - Jiaqi Li; Mingchao Wang; Kai Qu; Yuyao Sun; Zequn Yin; Na Dong; Xin Sun; Yitong Xu; Liang Chen; Shuang Zhang; Xunde Xian; Suowen Xu; et al. (Acta Pharmaceutica Sinica B)
Hypercholesterolemia is a significant risk factor for the development of atherosclerosis. 2′,3′,5′-Tri-O-acetyl-N6-(3-hydroxyphenyl) adenosine (IMM-H007), a novel AMPK agonist, has shown protective effects in metabolic diseases. However, its impact on cholesterol and triglyceride metabolism in hypercholesterolemia remains unclear. In this study, we aimed to elucidate the effects and specific mechanisms by which IMM-H007 regulates cholesterol and triglyceride metabolism. To achieve this goal, we used Apoe−/− and Ldlr−/− mice to establish a hypercholesterolemia/atherosclerosis model. Additionally, hepatocyte-specific Ampka1/2 knockout mice were subjected to a 5-week high-cholesterol diet to establish hypercholesterolemia, while atherosclerosis was induced via AAV-PCSK9 injection combined with a 16-week high-cholesterol diet. Our results demonstrated that IMM-H007 improved cholesterol and triglyceride metabolism in mice with hypercholesterolemia. Mechanistically, IMM-H007 modulated the AMPKα1/2–LDLR signaling pathway, increasing cholesterol uptake in the liver. Furthermore, IMM-H007 activated the AMPKα1–FXR pathway, promoting the conversion of hepatic cholesterol to bile acids. Additionally, IMM-H007 prevented hepatic steatosis by activating the AMPKα1/2–ATGL pathway. In conclusion, our study suggests that IMM-H007 is a promising therapeutic agent for improving hypercholesterolemia and atherosclerosis through the activation of AMPKα.